Chemical Characterization of Reproduction Cork from Spanish Quercus Suber (Journal of Wood Chemistry and Technology, 1998)
Abstract The chemical composition of Quercus suber reproduction cork was studied in planks from three different trees at different stages of their industrial processing and in samples collected in seven locations in the three main Spanish production areas. Extracts in chloroform, methanol and water, ne[ugrave]tral and acid fractions of waxes, suberin, lignin, holocellulose and pentosans, and polyphenols (low molecular weight polyphenols and tannins), were quantified. Suberin was the main component in all the samples, followed by lignin and holocellulose in lower concentrations. The most affected variables throughout the industrial processing were: lignin, chloroform and water extracts and the acid fraction of waxes. These variables did not allow one to distinguish the studied trees, which are differentiated by the percentages of methanol extracts, the tannic fraction of polyphenols, the free of suberin residue and the holocellulose content. Four variables were selected as those which provided the greatest discrimination among provenances: methanol extract, low molecular weight polyphenols, desuberinized residue and acid fraction of waxes. However, the studied populations can not be clearly distinguished by their chemical composition and no relationship was found between geographical proximity of their provenances and chemical resemblance.
doi: 10.1080/02773819809349592